2020
DOI: 10.3390/sym12010161
|View full text |Cite
|
Sign up to set email alerts
|

Research on Collaborative Planning and Symmetric Scheduling for Parallel Shipbuilding Projects in the Open Distributed Manufacturing Environment

Abstract: In the current distributed manufacturing environment, more extensive enterprise cooperation is an effective means for shipbuilding companies to increase the competitiveness. However, considering the project scale and the uneven production capacity between the collaborative enterprises, a key issue for shipbuilding companies is to effectively combine the product-oriented project tasks and the specialized production-oriented plants. Due to information privatization, the decision-making process of project plannin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 71 publications
0
4
0
Order By: Relevance
“…considered the multi-mode project scheduling problem and evaluated the efficiency of each mode in terms of time, cost, quality, and environmental impacts [22]. Mao et al (2020) Presented a mathematical model in shipbuilding project scheduling problem. There are several projects (multi-projects) in order to execute in their model.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…considered the multi-mode project scheduling problem and evaluated the efficiency of each mode in terms of time, cost, quality, and environmental impacts [22]. Mao et al (2020) Presented a mathematical model in shipbuilding project scheduling problem. There are several projects (multi-projects) in order to execute in their model.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Decreasing the cost and increasing the quality was the objective functions of shipbuilding project problem. The findings showed the distributed scheduling process can be effectively connected by parameterizing the local optimization and the interorganizational coordination process [23]. Panwar and Neeraj Jha (2021) used the NSGA-II algorithm to deal with the TCQ trade-off problem considering safety issues [24].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Enterprise management is a large area composed of different elements, and the symmetry of different elements generally exists in enterprise management. Numerous studies have shown that the symmetry of different elements of enterprise management plays a synergistic role in promoting enterprise development [1][2][3]. This idea is also applicable to the diversification strategies of enterprises.…”
Section: Introductionmentioning
confidence: 98%
“…Shipbuilding projects possess distinct characteristics such as complex product structures, multiple manufacturing stages, long production cycles, tight deadlines, jobbing work, concurrent execution of multiple projects, frequent modifications in engineering designs, and so on (Mao et al, 2020). Effective production planning plays a crucial role as it directly impacts construction costs and project duration.…”
Section: Introductionmentioning
confidence: 99%